Explaining mantras : ritual, rhetoric, and the dream of a natural language in Hindu tantra - Yelle, Robert A. (New York : Routledge, 2003)
Explaining Mantras explores the intersection of poetry and magic in the mantras or verbal formulas of Hindu Tantra and combines the study of ancient Tantric rituals with the latest theories in the human sciences.
Introduction: The Word and the World -- Ch. 1. Opening the Puzzle Box: Mantras, Poetry, and Magic -- Ch. 2. Chanting the Cosmogony: Mantras as Diagrams of Creation -- Ch. 3. The Linguistic Ideology of the Tantras: Language, Canon, and Idolatry -- Ch. 4. The Science of Illusion, Part One: Poetry and the Dream of a Natural Language -- Ch. 5. The Science of Illusion, Part Two: The Rhetoric of Ritual -- Ch. 6. Toward a Genealogy of Ritual and Rhetoric: Iconophiles and Iconophobes.
Includes bibliographical references (pages 165-177) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Tantras -- Criticism, interpretation, etc; Tantras; Hindu mantras; Mantras (Hindouisme); RELIGION -- Hinduism -- General; Hindu mantras; Multi-User: limited to 5 simultaneous users; Electronic books; Criticism, interpretation, etc